2015
DOI: 10.2495/rm150011
|View full text |Cite
|
Sign up to set email alerts
|

Rivers and river basin management issues and concerns in the Pacific Northwest, USA

Abstract: Over 90% of Pacific Northwest residents consider clean rivers and effective river basin management to be important issues in the Pacific Northwest. The large Columbia-Snake River Basin provides irrigation water to 5,000,000 ha, water for navigation, drinking water to more than 5,000,000 people and electricity (hydropower) to more than 8,000,000 people within Washington, Idaho, Oregon and British Columbia. The purpose of this paper is to document public perceptions, attitudes, and concerns about the Columbia-Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Four mailings were planned to achieve the 50% return rate [10,11]. The mailing strategy used was identical in all eight surveys that had been conducted in the region since 1998 [1,2,3,4]. It only took three mailings to achieve the target return rate of 50% in 2002, 2005, 2007, 2012 and 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four mailings were planned to achieve the 50% return rate [10,11]. The mailing strategy used was identical in all eight surveys that had been conducted in the region since 1998 [1,2,3,4]. It only took three mailings to achieve the target return rate of 50% in 2002, 2005, 2007, 2012 and 2015.…”
Section: Methodsmentioning
confidence: 99%
“…The public in the PNW are aware of the high quality and sufficient quantity of their water resource [1,2,3,4,5]. Studies have shown that a significant portion of public are interested in water and that they access water information on the Internet [6].…”
Section: Introductionmentioning
confidence: 99%
“…This system is key to the economies of British Columbia, Washington, Idaho, Oregon and Montana as it supports agriculture (5,000,000 irrigated ha), commerce, power production, direct human water consumption, food processing and recreation. Previously conducted surveys have shown than that the public within the region consider water their most important natural resource and that there are significant concerns about both water quality and water quantity issues within this large river basin [1]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…Four mailings were planned to achieve the 50% return rate [15], [16]. The mailing strategy used was identical in all six surveys that had been conducted in the region since 1970 [1]- [4].…”
Section: Introductionmentioning
confidence: 99%